Immunologic function in a cohort of human immunodeficiency virus type 1-seropositive and -negative healthy homosexual men. - Klimas, N G (1991)
The study objectives were to determine the early effects of human immunodeficiency virus type 1 (HIV-1) infection on both phenotypic and functional immunologic markers in healthy homosexual men, to ascertain the relationships of these markers to each other, and to discover which markers were affected by enrollment in an AIDS study in which HIV-1 serostatus would be determined. The major findings were as follows. (i) The CD4/CD8 ratio and lymphocyte proliferative response to pokeweed mitogen were the characteristics most affected by early HIV-1 infection. (ii) The loss in CD4 cells observed in the HIV-1-positive homosexual men was entirely due to diminished numbers of the memory subset. CD4+ CD29+. The reciprocal subset of CD4, CD4+ CD45RA+, did not differ in the two groups of homosexual men at either time point or in the controls. (iii) Prior to learning their HIV-1 serostatus, HIV-1 antibody-negative risk-group males had lower phytohemagglutinin (PHA) responses than the controls did. In the assays following notification of their seronegativity, however, these men had PHA values which were not different from those of the controls. In the HIV-1-positive group, the responses to both PHA and pokeweed mitogen were below those of both HIV-1-negative groups and did not change after serostatus notification. (iv) The activity of natural killer cells was lower in the risk-group men than in the controls at both pre- and postdiagnosis but was not related to HIV-1 serostatus. (v) In this cohort of homosexual men, the CD4/CD8 ratio correlated significantly with the functional measures of immunologic status in the HIV-1-positive men, but not in the HIV-1-negative men.